Analysis of fault slip potential of active faults in Tangshan seismic region after the Tohoku-Oki 3.11 M9.0 earthquake based on in situ stress monitoring data - Fan, Yulu; Zhang, Peng; Feng, Chengjun; Meng, Jing; Qi, Bangshen; Wang, Jiming; Tan, Chengxuan (Frontiers in Earth Science, 2022)
In order to ascertain the impact of the Tohoku-Oki 3.11 M9.0 earthquake on the stability of the faults in the Tangshan seismic region, we investigated the adjustment of the in situ stress field of the seismic region after this earthquake based on in situ stress monitoring data. Then, according to the Mohr-Coulomb failure criteria and Byerlee’s law, we used the FSP v.1.0 software package to calculate the fault slip potential (FSP) of the main faults in the seismic region at each adjustment stage of the in situ stress field, and to study the risk of fault activity. The research results show that 1) after the Tohoku-Oki 3.11 M9.0 earthquake, the tectonic environment of the Beijing Plain area changed rapidly from nearly EW extrusion to nearly EW extension, and this state was maintained until June 2012. After this, it began to gradually adjust to the state present before the earthquake. As of September 2019, at the depth of 100m, the maximum horizontal principal stress value in Tangshan seismic region was 7.61–7.81MPa, the minimum horizontal principal stress value was 5.30–5.50MPa, and the maximum horizontal principal stress orientation was N55.1°–59.5°E. (2) Before the Tohoku-Oki 3.11 M9.0 earthquake, the stress accumulation level of the main faults in the seismic region was relatively high with the FSP values of 30–60%. After this earthquake, the stress accumulation level of each fault continued to decrease, as of May 2013, the FSP values were mainly concentrated at 10–35%. Then, the stress accumulation level of major faults in the seismic region began to gradually increase. As of September 2019, the FSP values were mainly concentrated at 23–37%, and the stress accumulation level was still lower than the pre-earthquake state. 3) The fault activity in the central and northern parts of the seismic region was the strongest, followed by the southern part and western part, and the fault activity in the eastern part was the weakest.